Compact high‐power millimetre wave sources driven by pseudospark‐sourced electron beams. Issue 11 (21st June 2019) - Yin, Huabi; Zhang, Liang; Xie, Jie; Ronald, Kevin; He, Wenlong; Shu, Guoxiang; Zhao, Junping; Yin, Yong; Chen, Xiaodong; Alfadhl, Yasir; Phelps, Alan D.R.; Cross, Adrian W.
Abstract : This article presents the demonstration of several compact millimetre wave sources driven both by a pencil or sheet electron beam from a pseudospark (PS) discharge. The millimetre wave sources include two pencil beam extended interaction oscillators (EIO) in W‐band (75–110 GHz), two sheet beam EIOs in W‐ and G‐bands, two pencil beam backward wave oscillators (BWO) in W‐ and G‐bands, and one pencil beam Cherenkov maser in Ka‐band. These devices can generate up to kilowatts of output power, which are very attractive for many important applications.